Prediction of Protein-Protein Interaction Strength Using Domain Features with Supervised Regression. (24th June 2014) - Kamada, Mayumi; Sakuma, Yusuke; Hayashida, Morihiro; Akutsu, Tatsuya
Abstract : Proteins in living organisms express various important functions by interacting with other proteins and molecules. Therefore, many efforts have been made to investigate and predict protein-protein interactions (PPIs). Analysis of strengths of PPIs is also important because such strengths are involved in functionality of proteins. In this paper, we propose several feature space mappings from protein pairs using protein domain information to predict strengths of PPIs. Moreover, we perform computational experiments employing two machine learning methods, support vector regression (SVR) and relevance vector machine (RVM), for dataset obtained from biological experiments. The prediction results showed that both SVR and RVM with our proposed features outperformed the best existing method.